Physician training in self-efficacy enhancing interviewing techniques (SEE IT): Effects on patient psychological health behavior change mediators. Issue 11 (November 2016) - Jerant, Anthony; Lichte, Melissa; Kravitz, Richard L.; Tancredi, Daniel J.; Magnan, Elizabeth M.; Hudnut, Andrew; Franks, Peter
Highlights: We explored patient effects of self-efficacy enhancing interviewing techniques. Outcomes were self-care self-efficacy, readiness, and health locus of control. We examined the outcomes as a standardized summary score and individually. Patients visiting SEE IT-trained physicians had an improved summary score. They also had improved readiness and reduced Chance health locus of control. Abstract: Objective: To explore how physician training in self-efficacy enhancing interviewing techniques (SEE IT) affects patient psychological health behavior change mediators (HBCMs). Methods: We analyzed data from 131 patients visiting primary care physicians ≥4 months after the physicians participated in a randomized controlled trial. Experimental arm physicians (N = 27) received SEE IT training during three ≤20 min standardized patient instructor (SPI) visits. Control physicians (N = 23) viewed a diabetes medications video during one SPI visit. Physicians were blinded to patient participation. Outcomes were self-care self-efficacy, readiness, and health locus of control (Internal, Chance, Powerful Others), examined as a summary HBCM score (average of standardized means) and individually. Analyses adjusted for pre-visit values of the dependent variables. Results: Patients visiting SEE IT-trained physicians had higher summary HBCM scores (+0.42, 95% CI 0.07–0.77; p = 0.021). They also had greater self-care readiness (AOR 3.04, 95% CI 1.02–9.03, p = 0.046) and less Chance health locus of control (−0.27 points, 95% CI −0.50–0.04, p = 0.023), with no significant differences in other HBCMs versus controls. Conclusion: Improvement in psychological HBCMs occurred among patients visiting SEE IT-trained physicians, Practice implications: If further research shows the observed HBCM effects improve health behaviors and outcomes, SEE IT training might be offered widely to physicians.